Tastes better than expected: Post-intervention effects of a vegetarian month in the student canteen - Charlotte Klatt; Anna Schulze Tilling (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Interventions to decrease meat consumption are often only implemented for short periods of time, and it is unclear how they might have lasting effects. We combine student canteen consumption (over 270, 000 purchases made by over 4, 500 guests) and survey data (N > 800) to study how a one-month intervention to decrease meat consumption affects consumer behavior post-intervention. During the intervention period, meat meals were eliminated from the menu of the treatment canteen, while the two control canteens were unaffected. Using a difference-in-difference approach, we estimate that guests usually frequenting the treatment canteen did not significantly reduce their visits to the canteen during or after the intervention. In the two months following the intervention, they were still 4% less likely to choose the meat option when visiting the canteen, relative to baseline. A large part of this effect seems explicable with guests learning about the quality of the canteen's vegetarian meals. We find little to no evidence of the intervention changing perceived social norms.
Keywords: C93; D12; D83; Q18; 330; food consumption; behavioral intervention; field experiment; habit formation; experience